The effect of oxidation of wood particles on the usage quantity of adhesive and study the physical and mechanical properties of single layer particle board - parisa azari (Regional Information Center for Science and Technology (RICeST), 2014)
In this study the effect of surface oxidation of wood particles in order to reducing amount of adhesive for making single layer particleboard was investigated. Oxidation of wood particles cause to form carboxylic groups and free phenolic radicals that lead to activate the surface of wood particles for adhesion. This search was conducted on Populus nigra wood particles that they were oxidized by nitric acid (40%) including 0, 2, 4 and 6 percent (based on OD weight of wood). These wood particles were adhered by phenol formaldehyde resin in three amounts of 3, 5 and 7 percent (based on OD weight of wood) then wood particle cakes pressed in 180 degree of centigrade, 5 min and 30 kg/cm2. The results indicate that maximum MOR, MOE and minimum water absorption and swelling thickness was observed in boards with 7% adhesive and 4% acid. Using 5% adhesive and 4% acid had the best performance on shearing strength.